Prevalence, Molecular Identification and Antibiogram Profile of Neisseria gonorrhoeae among Individuals in Yenagoa, Bayelsa State, South South, Nigeria - Salvage, Akpomedaye; Imarenezor, Edobor Peter Kenneth; Anyiam, Vivian Ifeoma; Edafe, Ejiro Patrick (Darul Yasin Al Sys, 2024)
Neisseria gonorrhoeae (N. gonorrhoeae), the bacterium causing gonorrhea, is a global public health concern, particularly in Nigeria, due to its increasing antibiotic resistance. Its often asymptomatic nature leads to under diagnosis, continued transmission, and severe complications like infertility and pelvic inflammatory disease. The objectives of this study are to investigate the prevalence, molecular identification and antibiogram profile N. gonorrhoeae among individuals in Yenagoa, Bayelsa State. A cross- sectional study was conducted with 288 participants from Federal Medical Centre and Silhouette Diagnostics Consultants, both in Yenagoa. Urethral swab from males and endocervical swab from females were collected for identification of the organism. Antibiotic susceptibility was tested using the Kirby-Bauer method. The results showed a 2.78% prevalence, with higher prevalence in males (4.76%) than in females (1.64%). Antibiogram results demonstrated high resistance to penicillin (100%), tetracycline (75%), and erythromycin (62.5%), while susceptibility was highest to ceftriaxone (100%), cefixime (87.5%), and azithromycin (62.5%). Molecular analysis identified the PorA gene in all eight isolates. Key risk factors included previous sexually transmitted infections, multiple sexual partners, and transactional sex. The conclusion emphasizes the need for new antibiotics and vaccines, improved diagnostics, safer sexual practices, and routine molecular surveillance to combat resistant strains. It recommends updating treatment protocols based on current antibiogram data and enhancing public health campaigns to raise awareness and prevent gonococcal infections.